Leadership of the school head in times of social isolation - Leżucha, Magdalena (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
Social isolation was a difficult period for students, parents, teachers, and especially for school managers, i.e. principals. They were faced with new challenges and difficulties, they had to reorganize their work and the functioning of the entire school. Remote management of an educational institution is not easy at all, especially since so far it has not been necessary. The directors had to face their own weaknesses, sometimes resulting from the lack of technical skills, but also as people they faced fear, fear for their lives, their families and employees. They were a support for teachers, students and parents in this extremely difficult period. This article is an attempt to understand what difficulties education managers had to face, how they dealt with it and whether they see the sense of working and managing a school at a distance in the future.